(untitled) (Progress Annals: Journal of Progressive Research, 2026)
This article analyzes trends in attracting foreign direct investment and the regional and institutional factors that affect their effectiveness. The study highlights the impact of regional development, the quality of the institutional environment, and governance factors on investment flows .